(untitled) (Universal International Scientific Journal, 2026)
This article scientifically analyzes the concepts of technical and tactical training in karate, their content and interrelationships. The research used methods of theoretical sources analysis, pedagogical observation and practical experience. The results showed that the integrated organization of technical and tactical training significantly increases the competitive effectiveness of athletes. The harmonious development of technical accuracy, speed and tactical thinking in the process of karate training is an important factor in achieving high sports results.